Design of CO2 Gas Measuring System - Arinto Yudi Ponco Wardoyo; Setyawan Purnomo Sakti; Didik Rahadi Santoso (Natural B, Journal of Health and Environmental Sciences, 2011)
Carbon dioxide (CO2) has been known well as a contributor gas for the global warming. Regarding the impact, the measurement of the CO2concentration in the air is very important for the assessment. This paper presents the design of a CO2 instrument built by using the components that are available in the market.  The instrument contains a CO2 sensor, an interfacing system, and a computer. The test showed that the instrument worked well. It could be used to measure a CO2 concentration on line and in real time.